Komunikasi Persuasif Pendeta Dalam Menyampaikan Firman Tuhan Di Media Sosial Instagram - Jeremia Engelita Wakas; Glory Virginia Sampel (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2021)
This study aims to understand persuasive communication by instagram account @philipmantofa as a pastor in conveying the Word of God. The focus of this research according to Cialdini’s six fundamental principles persuasive theory, such as reciprocation, commitment and consistency, social proof, liking, authority, and scarcity.This research also outlines communication persuasion element which are source, message, receiver, media, feedback and effect of communication persuasion. The research method uses descriptive qualitative methods with data collection techniques through observation, interviews with two sources who are instagram followers @philipmantofa, and document analysis. The results showed that the Chialdin’s six fundamental of principles persuasive applied by @philipmantofa and Digital communication team. Reciprocation, response from thousands of followers to the content that posted, showed he existence of external feedback. It was found that the lack of response from @philipmantofa and team about followers question in comment section. Commitment and consistency in post Word of God content. Social proof showed by significant amount of followers and keep increasing. Liking indicated by means of its own in making and presenting content that is in accordance with a lot of people interests. Instagram account @philimantofa have authority to persuade his followers because have believed by a lot of public. Scarcity give something unique and rare to strengthen the message with creative and innovative content.